The role of vicarious learning strategies in shaping consumers' uncertainty: the case of live-streaming shopping - Men, Jinqi; Zheng, Xiabing; Davison, Robert M. (Internet research, 2024)
PurposeThis article seeks to understand how live-streaming technology (i.e. interactivity and effective use of live-streaming shopping’s information presentation tool) impacts consumers’ credibility perception regarding live streamers.Design/methodology/approachThe authors empirically examined their hypotheses with data (n = 405) collected from a survey of consumers who engage in live-streaming shopping.FindingsThe results demonstrate that vicarious learning strategies (both coactive and independent) can shape consumers’ benefit perceptions (i.e. virtual presence and psychological proximity), and further have a positive effect on consumers’ personal value (i.e. perceived live streamer credibility). Furthermore, the consumers’ perception of the live streamers’ credibility positively affects their purchase intention and ultimately influences their purchase behavior.Originality/valueBuilding on the vicarious learning theory and means-end chain (MEC) model, this study investigates the mechanism of the IT features of live-streaming shopping in reducing consumers’ uncertainty about live streamers. This study reveals the value of vicarious learning experiences in reducing consumers’ uncertainty and further enhancing their purchase behavior.